Fishermen dressing and packing halibut on dock, Ketchikan, Alaska, October 3, 1910 - Cobb, John N. (John Nathan), 1868-1930 (1910)
From John Cobb field notebook: Dressing and packing halibut, Ketchikan. Oct. 3, 1910